Effects of Wenfei Guyuan umbilical moxibustion on patients with stable chronic obstructive pulmonary disease: A multicenter randomized controlled trial - Qionghua Xiao; Yuanyuan Meng; Gaoming Wang; Minghang Wang; Yong Meng; Miao Zhou (Complementary Therapies in Medicine)
Background: Chronic obstructive pulmonary disease (COPD) is a common chronic respiratory disease. Its high disability rate, high mortality rate, and heavy economic burden have made it a major public health problem. Umbilical moxibustion has been reported to have therapeutic effects on COPD, but there is a lack of high-quality evidence-based studies on this intervention. Therefore, the purpose of this study is to evaluate the efficacy and safety of Wenfei Guyuan (WFGY) umbilical moxibustion in the treatment of COPD. Methods: This was a multicenter, open-label, randomized controlled trial (RCT). A total of 220 participants were randomly assigned at a 1:1 ratio to the experimental group (WFGY umbilical moxibustion in combination with conventional drugs) and the control group (conventional drugs). Both groups received 13 weeks of treatment, followed by 26 weeks of follow-up. The primary outcome was the frequency of acute exacerbations, and the secondary outcomes were the 6-minute walk distance (6MWD), modified Medical Research Council dyspnea scale (mMRC) score, clinical symptoms and signs scores, and lung function tests. Statistical analysis was performed using SPSS software (version 25.0). Results: A total of 220 participants were included in the study, and 215 participants completed the trial. There were significant time effects and group effects on the frequency of acute exacerbations (P < 0.001, P = 0.001), but no interaction effects (P = 0.406). Compared with the control group, the frequency of acute exacerbations in the experimental group was significantly reduced at 4 and 13 weeks of treatment and at 13 and 26 weeks of follow-up (P < 0.05). Among the secondary outcomes, there were significant time effects, group effects, and interaction effects on the 6MWD, mMRC scores, and clinical symptoms and signs scores (cough, expectoration, wheezing, chest tightness, shortness of breath, fatigue, cyanosis, and total scores) at different time points between the two groups (P < 0.05). FVC and FEV1 had no time effects, group effects, or interaction effects (P > 0.05). FEV1 % had group effects (P < 0.05) but no time effects or interaction effects (P > 0.05). The overall skin sensitization incidence in the experimental group was 3.74 %, which was slightly higher than the 0 % incidence in the control group, but no statistically significant difference was observed between the two groups (P > 0.05). Conclusions: The experimental group demonstrated superior efficacy to the control group in reducing the frequency of acute exacerbations, enhancing exercise tolerance, reducing dyspnea severity, and improving quality of life. This intervention demonstrated effectiveness and safety in the treatment of stable COPD, providing a foundation for further research. Trial registration: https://www.chictr.org.cn, ChiCTR2100049802. Registered on August 9, 2021.